(untitled) (Bangladesh Journal of Plant Taxonomy, 2005)
A total of 108 algal taxa belonging to 57 genera and nine classes (excluding Chlorophyceae), namely, Cyanophyceae 28, Euglenophyceae 37, Chloromonadophyceae 1, Charophyceae 3, Xanthophyceae 11, Chrysophyceae 4, Bacillariophyceae 20, Dinophyceae 2 and Rhodophyceae 2 have been recorded from some acidic habitats within the tea gardens at Srimangal, Maulvi Bazar. Of these 13 are new records for Bangladesh. Key words: Acidic habitats; diversity; phytoplankton; periphyton; new records DOI: 10.3329/bjpt.v12i1.609 Bangladesh J. Plant Taxon. 12(1): 33-52, 2005 (June)